PENGARUH KONSENTRASI SUKROSA DAN STARTER TERHADAP KARAKTERISTIK SUSU KACANG MERAH (Phaseolus vulgaris L.) FERMENTASI - Yanni Nathasia Br. Gurusinga; Jenny E.A. Kandou; Dekie Rawung Dekie Rawung (COCOS, 2020)
ABSTRACTThis research aims to find the formula of fermented red bean milk withadding sucrose concentration and different starter that can be accepted by thepanelist and to analyze the chemical content. The research was designed usingCompletely Randomized Design (CRD) with different sucrose concentration(Factor A) and starter (Factor B). A1B1 (2% Sucrose and 5% Starter), A1B2 (2%Sucrose and 10% Starter), A1B3 (2% Sucrose and 15% Starter), A2B1 (5%2Sucrose and 5% Starter), A2B2 (5% Sucrose and 10% Starter), A2B3 (5%Sucrose and 15% Starter), A3B1 (8% Sucrose and 5% Starter), A3B2 (8%Sucrose and 10 % Starter), A3B3 (8% Sucrose and 15% Starter) with 3replications. the observation parameters of Total Lactic Acid bacteria, Total Acid,Total Sugar, Degree of Acidity (pH), and Sensory Test (Color, Scent, Taste,Vulnerability). The result shows that A3B3 (8% Sucrose and 15% Starter) isaccepted by the panelist with total bacterial lactic acid content of 1.60 x 105 colon/ g, total acid 0.037%, total sugar is 8.42%, and pH 5.Keywords: Fermented milk, Red bean